2013
DOI: 10.1620/tjem.229.233
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Stereotype and Poor Working Condition Pose Obstacles for Female Doctors to Stay in Full-Time Employment: Alumnae Survey from Two Private Medical Schools in Japan

Abstract: The shortage of physicians has become a serious problem in Japan. It has been pointed out that an increase in the number of female doctors may contribute to the aggravation of this shortage because it is known that women work fewer hours than male doctors. Here, we investigated how many female doctors had ever resigned from a full-time position, and elucidated the reasons why female doctors find it difficult to stay in full-time employment. An alumnae survey of 2 private medical schools was conducted in 2007. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
0
20
1
Order By: Relevance
“…In Japan, it has been reported that out of a population of resigned female physicians, 90% resigned within 10 years of graduation from medical school. The difficulty in balancing work, and childbirth, and balancing work and raising children were the top 2 reasons for resignation, accounting for 45% of resignation …”
Section: Gender Stereotypes That Results In More Male Health Care Profmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, it has been reported that out of a population of resigned female physicians, 90% resigned within 10 years of graduation from medical school. The difficulty in balancing work, and childbirth, and balancing work and raising children were the top 2 reasons for resignation, accounting for 45% of resignation …”
Section: Gender Stereotypes That Results In More Male Health Care Profmentioning
confidence: 99%
“…The difficulty in balancing work, and childbirth, and balancing work and raising children were the top 2 reasons for resignation, accounting for 45% of resignation. 21 Pregnancy and family responsibilities prevent female health care professionals from pursuing more specialized leadership and management positions. Likewise, studies indicate that gender stereotypes persist in the health care workforce and that female health care professionals often choose specialties with lighter workloads that allow them to balance work and family.…”
Section: Gender Stereotypes That Results In More Male Health Care Prmentioning
confidence: 99%
“…This may explain the lack of support and understanding from colleagues when women become pregnant and may be one of the main reasons women leave work completely rather than take maternity leave. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that female doctors in Japan work fewer hours, retire earlier and are more likely to be professionally inactive, compared with their male counterparts. 4 A survey of 711 Japanese female doctors revealed that 55% had resigned from full-time positions at least once, and only 30% of these women returned to full-time employment. 5 It is known that women in Japan often stop working while in their 30s, after having had children, and then return to the workforce after they have finished raising their children.…”
Section: Introductionmentioning
confidence: 99%
“…However, this may not mean that there is less gender-based obstacles in the work environment for physicians in Japan. Female physicians in Japan are often faced with binary choice of family and career in the very early stages of their careers due to the double burden that stems from the long and erratic work hours, inadequate infrastructural child care support, and lack of spouses' participation in domestic work (Yasukawa and Nomura 2012;Izumi et al 2013). In a nationwide survey by the Japan Medical Association, 64.1% of female physicians reported that the biggest concern regarding their career was the difficulty of balancing career and family responsibilities (Japan Medical Association 2009).…”
Section: Discussionmentioning
confidence: 99%